2012
DOI: 10.1016/j.jnt.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Gauss sums over some matrix groups

Abstract: In this note, we give explicit expressions of Gauss sums for general (resp. special) linear groups over finite fields, which involve classical Gauss sums (resp. Kloosterman sums). The key ingredient is averaging such sums over Borel subgroups, i.e., the groups of upper triangular matrices. As applications, we count the number of invertible matrices of zero-trace over finite fields and we also improve two bounds of Ferguson, Hoffman, Luca, Ostafe and Shparlinski in [R. Ferguson, C. Hoffman, F. Luca, A. Ostafe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Recently, we obtained explicit expressions of S(GL n (F q ), U) and S(SL n (F q ), U). (See [12] Theorems 2.1 and 2.4). Such expressions only involve Gauss sums and Kloosterman sums.…”
Section: Preliminariesmentioning
confidence: 97%
“…Recently, we obtained explicit expressions of S(GL n (F q ), U) and S(SL n (F q ), U). (See [12] Theorems 2.1 and 2.4). Such expressions only involve Gauss sums and Kloosterman sums.…”
Section: Preliminariesmentioning
confidence: 97%
“…Note that this result should be compared with results of Ferguson et al, Li and Hu, and Karabulutin in the paragraph subsequent to Problem 1.3. In our result, we impose a stronger condition on E, F , i.e., E ⊆ D i and E ⊆ D j , than they did in [15,31,5] , while our threshold q 4 is much better than those in their results (for n = 2).…”
Section: Introductionmentioning
confidence: 64%
“…Ferguson et al [15] developed a version of the Kloosterman sum over matrix rings to prove that if |E||F | ≥ 2q 2n 2 −2 , then there exist elements x ∈ E and y ∈ F such that det(x + y) = 1. In the paper [31], Li and Hu gave an explicit expression of Gauss sum for the special linear group SL n (F q ), and as a consequence, they obtained an improvement of Ferguson et al's result. More precisely, they showed that if n = 2, then the condition |E||F | ≥ Cq 5 is enough, but in higher dimensional cases, we need |E||F | ≥ Cq 2n 2 −2n .…”
Section: Introductionmentioning
confidence: 93%
“…The usual way of computing n q (k × k, k, k) involves the Bruhat decomposition of GL k (F q ) and the theory of q-analogues (see [24], Proposition 1.10.15). A different approach proposed in [16] is based on Gauss sums over finite fields and properties of the Borel subgroup of GL k (F q ). In [2] Buckheister derived a recursive description for n q (k×k, r, k) using an elementary argument, and in [1] Bender applied the results of [2] to provide a closed formula for n q (k×k, r, k).…”
Section: Matrices With Given Rank and H-tracementioning
confidence: 99%